2019
DOI: 10.1002/cncy.22119
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up with histopathology and HPV testing on LSIL cytology in China’s largest academic woman’s hospital

Abstract: Background Cervical cancer remains a major health problem in China. To provide baseline data for establishing the appropriate screening strategy, the authors investigated the histopathologic follow‐up and human papillomavirus (HPV) testing results of low‐grade squamous intraepithelial lesion (LSIL) cytology in the Chinese Largest Women Hospital. Methods Women with LSIL cytology, human papillomavirus (HPV) testing, and immediate histopathologic follow‐up between 2011 and 2016 were analyzed. Results The frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
6
10
0
Order By: Relevance
“…The current study has demonstrated a similar result: conventional Pap testing has a comparable reporting rate and a slightly lower predicative value for predicting CIN‐2+ among the 3 preparation methods in the NILM group (reporting rate, 97.8% vs 94.2% for ThinPrep and 92.9% for SurePath; rate for predicting CIN‐2+, 1.4% vs 2.1% for ThinPrep and 2.1% for SurePath). These results also support the notion from our previous study that conventional Pap testing still remains a reasonable option in rural areas of China because of the limited resources, low cost, ease of setup, and relatively comparable performance …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study has demonstrated a similar result: conventional Pap testing has a comparable reporting rate and a slightly lower predicative value for predicting CIN‐2+ among the 3 preparation methods in the NILM group (reporting rate, 97.8% vs 94.2% for ThinPrep and 92.9% for SurePath; rate for predicting CIN‐2+, 1.4% vs 2.1% for ThinPrep and 2.1% for SurePath). These results also support the notion from our previous study that conventional Pap testing still remains a reasonable option in rural areas of China because of the limited resources, low cost, ease of setup, and relatively comparable performance …”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, we found that the conventional Pap preparation method has performance comparable to that of liquid‐based cytology for predicting CIN in Chinese women with low‐grade squamous intraepithelial lesion cytology. The current study has demonstrated a similar result: conventional Pap testing has a comparable reporting rate and a slightly lower predicative value for predicting CIN‐2+ among the 3 preparation methods in the NILM group (reporting rate, 97.8% vs 94.2% for ThinPrep and 92.9% for SurePath; rate for predicting CIN‐2+, 1.4% vs 2.1% for ThinPrep and 2.1% for SurePath).…”
Section: Discussionmentioning
confidence: 94%
“…These results are essentially in agreement with studies from Western countries and the benchmark ranges from the 2010 CAP survey in the United States 2 . In our previous studies, we observed that the CPT had performance comparable to that of liquid‐based cytology for predicting CIN2+ lesions in Chinese women who had negative cytology or low‐grade squamous intraepithelial lesion cytology 10,11 . The current study demonstrated that, although the CPT preparation method had the lowest reporting rate among the 3 methods, the performance of the CPT method for predicting CIN was comparable to the performance of the ThinPrep and SurePath methods (35.5% vs 35.9% and 32.1%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…The current study demonstrated that, although the CPT preparation method had the lowest reporting rate among the 3 methods, the performance of the CPT method for predicting CIN was comparable to the performance of the ThinPrep and SurePath methods (35.5% vs 35.9% and 32.1%, respectively). Similar to the observation from our earlier study, 10 the predictive value for detecting CIN2+ lesions was highest using the CPT method (12.0% vs 8.2% [ThinPrep] and 6.7% [SurePath]). These findings provide additional evidence that conventional Pap testing remains a reasonable option for Chinese women in the rural areas when the liquid preparation methods or HPV testing are not feasible, although at the cost of low sensitivity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation